Local Coastal Configuration Rather Than Latitudinal Gradient Shape Clonal Diversity and Genetic Structure of Phymatolithon calcareum Maerl Beds in North European Atlantic - Pardo, Cristina; Guillemin, Marie-Laure; Peña, Viviana; Bárbara, Ignacio; Valero, Myriam; Barreiro, Rodolfo (Frontiers in Marine Science, 2019)
Maerl beds are one of the world’s key coastal ecosystems and are threatened by human activities and global change. In this study, the genetic diversity and structure of one of the major European maerl-forming species, Phymatolithon calcareum, was studied using eight microsatellite markers. Two sampling scales (global: North East Atlantic and regional: Galicia) were investigated and fifteen maerl beds from Atlantic Europe were sampled. At the regional-scale the location of sites outside and within four estuaries allowed to test for the influence of coastal configuration on population connectivity and genetic diversity. Results suggested that clonal reproduction plays an important role in the population dynamics of P. calcareum maerl beds. Clonality was variable among populations, even within the same region. At the European scale, these differences in clonality cannot be explained by the geographic or latitudinal distribution of the populations studied. A significant genetic differentiation was found among almost all population pairs and a positive correlation between geographic and genetic distances showed the limited dispersal capacity of P. calcareum. Moreover, a very clear pattern of genetic structure was revealed at the regional scale between populations located within and at the mouth of the estuaries. Genetic differentiation among estuaries was less marked for the sites located in outer-zones compared to those located in the inner-zones. In addition, variation in level of clonality linked to seascape was also observed: populations situated in the outer-zones of the estuaries were less clonal than those in the inner-zones. Finally, populations from the same estuary generally shared one or several mutilocus genotypes.